Study of Top-Quark Production and Decays involving a Tau Lepton at CDF and Limits on a Charged-Higgs Boson Contribution - Collaboration, CDF; Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2014)
We present an analysis of top-antitop quark production and decay into a tau lepton, tau neutrino, and bottom quark using data from $9 {\rm fb}^{-1}$ of integrated luminosity at the Collider Detector at Fermilab. Dilepton events, where one lepton is an energetic electron or muon and the other a hadronically-decaying tau lepton, originating from proton-antiproton collisions at $\sqrt{s} = 1.96 TeV$ are used. A top-antitop quark production cross section of $8.1 ± 2.1 {\rm pb}$ is measured, assuming standard-model top-quark decays. By separately identifying for the first time the single-tau and the ditau components, we measure the branching fraction of the top quark into tau lepton, tau neutrino, and bottom quark to be $(9.6 ± 2.8) %$. The branching fraction of top-quark decays into a charged Higgs boson and a bottom quark, which would imply violation of lepton universality, is limited to be less than $5.9%$ at $95%$ confidence level.